An unusual clinical presentation of lupus erythematosus tumidus localized on the thigh. (1st August 2017) - Hashimoto, T.; Kawakami, Y.; Wakabayashi, H.; Oda, W.; Hamada, T.; Doi, H.; Aoyama, Y.; Iwatsuki, K.
Summary: A 44‐year‐old woman with seronegative polyarthritis presented with a 2‐year history of a solitary, bluish‐red, oedematous, nonscaly, annular and partially reticulated macule on her right thigh. Histopathological findings revealed perivascular and periadnexal lymphocytic infiltrate in the dermis. Alcian blue and colloidal iron stains highlighted mucinous deposit in the upper and mid dermis. Direct immunofluorescence showed a linear deposit of IgG and C3 along the basement membrane zone. Antinuclear antibody was positive at a titre of 1 : 80, with homogenous and speckled patterns. Except for its unusual localization and lack of photosensitivity, our case had the clinical and histopathological features of lupus erythematosus tumidus. These characteristics were also reminiscent of reticular erythematous mucinosis and erythema annulare centrifugum, both of which are considered to be associated with cutaneous lupus erythematosus (CLE). Hydroxychloroquine 200 mg daily led to improvement of the skin lesion. The unusual clinical presentation of our case emphasizes the heterogeneity of clinical manifestations of CLE.